PERBEDAAN AKTIVITAS FISIK, KADAR Hb, DAN KESEGARAN JASMANI (STUDI PADA SISWI KEK DAN TIDAK KEK DI SMA N 1 GROGOL KABUPATEN KEDIRI) - Wardhani, Juwita Pramodya; Rahfiludin, M. Zen; Pradigdo, Siti Fatimah (Jurnal Kesehatan Masyarakat (Undip), 2015)
Nutritional problem that often occurs to young women is the lack of nutrient intake which caused energy deficiency chronic. According to riskesdas 2007, Kediri risk prevalence of energy deficiency chronic up to 14.9%. The purpose of this study was to know the difference of physical activity, hemoglobin rate and physical fitness in energy deficiency chronic student and non energy deficiency chronic student. Study design of this research is analytic comparative study with cross sectional approach. Population for this study is female student of Senior High School 1 Grogol, Kediri in the 10th and 11th grade 401 in total. Study sample is 32 female students for each group. Using purposive sampling. Man – Whitney U test is used to analyze physical activity differentiation.Whereas hemoglobin and physical fitness differentiation is analyzed by Independent T Test. Result showed that physical activity ofenergy deficiency chronic student has no significant different (p=0,087) with non energy deficiency chronic student, Hemoglobin rate for energy deficiency chronic student has significant different (p=0,027) with non energy deficiency chronic student and physical fitness for energy deficiency chronic student has nosignificant different (p=0,074)with non energy deficiency chronic student. Conclusion of the research is There is no difference between physical activity and physical fitness while hemoglobin rate gives significant difference to energy deficiency chronic student and non energy deficiency chronic student. Recommended for the health department regarding to the procurement of Fe tablet and socialization on the impacts and prevention of anemia for the prevention of anemia in adolescence.